2007
DOI: 10.1007/s10562-007-9192-8
|View full text |Cite
|
Sign up to set email alerts
|

Na2WO4/Co–Mn/SiO2 Catalyst for the Simultaneous Production of Ethylene and Syngas from CH4

Abstract: Na 2 WO 4 /Co-Mn/SiO 2 catalyst was prepared and used for the simultaneous production of ethylene and syngas from CH 4 . A CH 4 conversion of 38% and a yield of 21% for (C 2 H 4 + CO), with a C 2 H 4 /CO/H 2 ratio of 1/0.7/ 0.7 were obtained under the optimized conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…From Table , it was found that higher flow velocity favored the formation of CO and decreased the selectivity of C 2 H 4 . This is in agreement with the results in our previous report . The selectivity of H 2 , decreasing along with the increasing flow velocity, reached a minimum of 4.6% at F = 120 mL/min and then increased with further increase of flow velocity.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…From Table , it was found that higher flow velocity favored the formation of CO and decreased the selectivity of C 2 H 4 . This is in agreement with the results in our previous report . The selectivity of H 2 , decreasing along with the increasing flow velocity, reached a minimum of 4.6% at F = 120 mL/min and then increased with further increase of flow velocity.…”
Section: Resultssupporting
confidence: 93%
“…This is in agreement with the results in our previous report. 29 The selectivity of H 2 , decreasing along with the increasing flow velocity, reached a minimum of 4.6% at F ) 120 mL/min and then increased with further increase of flow velocity. It seems that when F e 120 mL/min, CO 2 and H 2 O stay a longer time in the second catalyst bed, and then the reforming reaction C 2 H 6 + 2H 2 O f 2CO + 5H 2 and C 2 H 6 + 2CO 2 f 4CO + 3H 2 occurred more sufficiently.…”
Section: Influence Of Flow Velocity On the Resultsmentioning
confidence: 90%
“…Fang et al [19,20] first reported the Na 2 WO 4 /Mn/SiO 2 catalyst for OCM in 1992, 37.7% CH 4 conversion and 66.9% C 2 selectivity were achieved at 800°C in a microreactor. Then this system has received increasing attention for its excellent catalytic performance [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative coupling of methane (OCM) to C 2 + hydrocarbons has been intensively studied since 1980s, as one of the important potential routes to a possible future production of basic chemicals and liquid fuels from natural gas [1][2][3][4][5][6][7][8][9][10]. The reaction mechanism of OCM is very complicated and considerable controversies concerning the nature of the active centre in the catalyst exist.…”
Section: Introductionmentioning
confidence: 99%